The Influence of Financial Ratios on Financial Distress in the Consumer Goods Sector (2020-2024) - Mayzuroh, Dhila; Sri Rahayu; Pitaloka Dharma Ayu (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Economic growth in recent years, accompanied by increasingly fierce business competition and the lingering impact of the COVID-19 pandemic, has increased the vulnerability of companies in the consumer goods sector to financial distress. This situation is often reflected in weakening profitability, constrained liquidity, and rising pressure from debt obligations, which makes it essential to understand the key factors that may contribute to a company's financial instability. This study investigates the extent to which firm size, profitability, liquidity, and debt policy influence financial distress among consumer goods companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using a quantitative approach with a causal-associative design, the research draws on data from 34 companies, generating a total of 170 observations selected through purposive sampling. The analysis employs multiple linear regression assisted by SPSS 25, supported by classical assumption testing, t-tests, F-tests, and the coefficient of determination to evaluate the relationships between variables. The findings reveal that profitability and liquidity significantly affect financial distress, suggesting that firms with stronger earnings performance and healthier liquidity positions are better equipped to withstand financial pressures. In contrast, firm size and debt policy do not exhibit a significant partial effect on financial distress, although the overall model indicates that all four variables jointly exert a meaningful influence. These results underscore the importance of maintaining solid profitability and liquidity as a buffer against financial distress, while also highlighting that firm size and debt levels must be managed carefully to mitigate potential financial risks.